Spatiotemporal analysis of land use changes and their trade-offs on the northern slope of the Tianshan Mountains, China - Ma, Haitao (Frontiers in Ecology and Evolution, 2022)
The unprecedented urbanization recently has inevitably intensified the changes in land use morphology. However, current studies on land use primarily analyze a single morphology, ignoring the relationships between different land use morphologies. Taking the northern slope of the Tianshan Mountains (NSTM) as the study area, this article quantifies the spatiotemporal pattern of land use change, and estimates trade-offs and synergies between dominant (patch density, largest patch index, and landscape shape index) and recessive (land use efficiency, land use intensity, and agricultural non-point source pollution) morphologies to fully understand the dynamic characteristics of land use. Results showed bare areas and grassland were always predominant land use types, and land use change from 1990 to 2020 was characterized by the increase of impervious surfaces and the decrease of bare areas. The strongest trade-off was found between largest patch index and land use intensity, while the synergy between landscape shape index and land use intensity was strongest. There are significant disparities in terms of temporal and spatial patterns of trade-offs/synergies. The correlation coefficients in different study periods were much smaller than their estimations in the whole region, and the trade-offs/synergies in the eastern NSTM were basically identical with the whole relationships. The findings reveal the interactions among various land use characteristics, and provide significant references for coordinated land management and regional high-quality development.